Transformative Research Journey from Frustrated Learners to Critically Reflective Practitioners - Aryal, Rameshower (Journal of Transformative Praxis, 2023)
The conventional linear model of pedagogical practices promotes subject-centric memorizing, considering learners as knowledge recipients rather than generators of knowledge. This pedagogical practice degrades educational values by ignoring alternative inquiry-based visionaries and meaning-making approaches. Different forms of art in pedagogy, such as poetry, autobiographical reflection, and visual arts (i.e., paintings and cartoons) that capture learners' personal experiences, on the other hand, might be considered as one of the alternative models for a meaningful and critical understanding of the core and complex phenomena of the diverse world. Thus, the paper investigates the traditional linear pedagogical model and the critical transformative model utilizing Habermasian Knowledge's consecutive interests (technical, practical, and emancipatory) as the theoretical referent and metaphors for critical discourses of such pedagogical practices.